The Influence of Emotional Regulation and Cognitive Flexibility on Sleep Habits in Spanish Children and Adolescents through the Lens of Parents - Borja Costa-López; Rocío Lavigne-Cerván; Joshua A. Collado-Valero; Rocío Juárez-Ruiz de Mier; Ignasi Navarro-Soria (MDPI AG, 2023)
Background: Previous research studies have suggested the importance of studying the relationship between emotional regulation and sleep habits. Some investigations have especially focused on how emotional regulation could impact sleep habits in children and adolescents. Therefore, these researchers have stated there exists a two-way direction in this relationship. Objective: This study aimed to analyze the influence of emotional regulation on sleep habits in Spanish children and adolescents and the mediating role of anxiety in this relationship. Method: Participants were 953 Spanish parents who completed the assessment protocol according to their children and adolescents' information. Results: The results revealed moderate-strong correlations between emotional regulation problems and sleep habit disturbances (r = 0.375, p < 0.001), trait (r = 0.488, p < 0.001) anxiety, and state (r = 0.589, p < 0.001) anxiety. Additionally, emotional regulation showed a direct impact on sleep habits (β = 0.011, p = 0.005). Trait and state anxiety demonstrated a significant mediating role in the relationship between emotional regulation and sleep habits. Conclusions: Emotional regulation may have an impact on sleep habits during childhood and adolescence, suggesting the importance of early intervention focused on the emotions management and the prevention of sleep habit disturbances.